2020
DOI: 10.1021/acsbiomaterials.0c00188
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenol Microparticles Based on the Oxidative Coupling of EGCG Inhibit Amyloid Aggregation/Cytotoxicity and Serve as a Platform for Drug Delivery

Abstract: The accumulation of cross-β-sheet amyloid fibrils is a hallmark of all human amyloid diseases. The compound epigallocatechin-3-gallate (EGCG), the main polyphenol present in green tea, has been described to have beneficial effects in several pathologies, including amyloidogenic diseases. This polyphenol blocks amyloidogenesis and disaggregates a broad range of amyloidogenic peptides comprising amyloid fibrils in vitro. The mechanism by which EGCG acts in the context of amyloid aggregation is not clear. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Although no information is yet available to explain its mechanism of action on (i)sAPPβf, several data suggest that EGCG reduced the toxicity of amyloidogenic polypeptides by directly binding with unfolded protein and inhibiting the formation of β-sheet structure, an early event of amyloid formation cascade. At the molecular level, auto-oxidized EGCG reacts with free primary amine groups of proteins, forms a Schiff base, and induces fibril remodeling [ 37 , 38 ]. Interestingly, this mechanism not only might be operative with Aβ and TAU [ 39 ] in AD but also to other neurodegenerative disorders such as α-synuclein (in Parkinson’s disease), Huntingtin protein (in Huntington’s disease), and islet amyloid polypeptide (IAPP, amylin) in the pancreas most probably through a common mechanism, in which EGCG binds to cross-beta sheets amyloid aggregation intermediates remodeling the oligomeric amyloid or pre-formed amyloid fibrils into non-amyloidogenic species [ 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no information is yet available to explain its mechanism of action on (i)sAPPβf, several data suggest that EGCG reduced the toxicity of amyloidogenic polypeptides by directly binding with unfolded protein and inhibiting the formation of β-sheet structure, an early event of amyloid formation cascade. At the molecular level, auto-oxidized EGCG reacts with free primary amine groups of proteins, forms a Schiff base, and induces fibril remodeling [ 37 , 38 ]. Interestingly, this mechanism not only might be operative with Aβ and TAU [ 39 ] in AD but also to other neurodegenerative disorders such as α-synuclein (in Parkinson’s disease), Huntingtin protein (in Huntington’s disease), and islet amyloid polypeptide (IAPP, amylin) in the pancreas most probably through a common mechanism, in which EGCG binds to cross-beta sheets amyloid aggregation intermediates remodeling the oligomeric amyloid or pre-formed amyloid fibrils into non-amyloidogenic species [ 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased bioavailability of these particles may be important to reduce the required concentration of EGCG in promoting benefits and its future success in clinical trials ( Smith et al, 2010 ). New types of nanoparticles containing EGCG have been evaluated for their ability to inhibit amyloid aggregation ( Zhang J. et al, 2014 ; Debnath et al, 2016 ; Liu et al, 2017 ; Li et al, 2018 ; Singh et al, 2018 ; Fernandes et al, 2020 ). Selenium nanoparticles bound to EGCG and coated by the TET-1 peptide, which increases their delivery to neuronal cells, were effective at inhibiting amyloid cytotoxicity, blocking the Aβ aggregation and disaggregating mature fibrils ( Zhang J. et al, 2014 ).…”
Section: Drug Delivery Systems Containin Epigallocatechin-gallatementioning
confidence: 99%
“…Finally, a different concept was introduced by the synthesis of functional spheres of EGCG, synthesized by a simple method of catechin auto-oxidation under controlled heating and in the presence of a specific metal concentration ( Chen et al, 2013 ). These functional microparticles, with oxidized EGCG as carrier, have been shown to inhibit α-syn aggregation, reduce the cytotoxicity of oligomers and, modestly, remodel mature fibrils ( Fernandes et al, 2020 ). Moreover, when the EGCG microparticle was loaded with an additional amyloidogenesis inhibitor, ortho-iminoquinone ( Largeron and Fleury, 2012 ; Fernandes et al, 2017 ), its activity increased, demonstrating a synergistic action between the microcarrier and the loaded molecule ( Fernandes et al, 2020 ).…”
Section: Drug Delivery Systems Containin Epigallocatechin-gallatementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another study from 2013 noted that oxidized EGCG can be useful to fabricate drug delivery microparticles from naturally reproducible and edible green tea [236]. More recently, it was demonstrated that green tea polyphenol microparticles based on the oxidative coupling of EGCG inhibit amyloid aggregation/cytotoxicity of the protein α-syn and serve as a platform for drug delivery [219]. The study proposed using EGCG microparticles as a possible bifunctional strategy, blocking amyloidogenesis directly and carrying a molecule that can act synergistically to potentiate the anti-amyloidogenic effect [219].…”
Section: Egcg Targeting Misfolded Aggregates In Ad and Pdmentioning
confidence: 99%